Parental education and attitudes towards institutionalization of children in West Java, Indonesia - Michelle Andrina; José Ignacio Nazif-Muñoz; Rebecca Smith; Alice Shirley; Tata Sudrajat; Andri Yoga Utami; Mónica Ruiz-Casares (Child Protection and Practice)
Background: In low- and middle-income countries, orphanages are often perceived as a means to secure education for children. Consequently, many parents send their children to orphanages, unaware of the potential risks involved. Objective: This study aims to explore caregivers' attitudes toward child institutionalization in the context of placing children in orphanages. Participants: Data were collected from 736 caregivers of children aged 0–7 years in Cianjur, West Java, Indonesia, in 2017. Methods: Descriptive analysis and logistic regression were used to assess caregivers’ attitudes and the likelihood of agreeing or disagreeing with six statements about child institutionalization. Results: The study found that most caregivers agreed that poor children are better off being raised in orphanages, but parents remain responsible for the child even after placement. Logistic regression showed that caregivers with higher levels of formal education were less likely to agree with placing children in orphanages compared to caregivers with lower levels of formal education. Conclusions: This study highlights the importance of higher formal education in reducing caregiver support for institutionalization.